CONTRIBUTION OF MASARA N’ARZIKI PROGRAMME IN ALLEVIATING FARMERS` POVERTY IN NORTHERN REGION OF GHANA - Tanko, Mohammed (PEOPLE: International Journal of Social Sciences, 2017)
Small hold farmers` access to credit and the eradication of poverty among rural dwellers is the focus of many development agencies. Masara N’arziki Programme is an input credit project established in Northern region of Ghana with the aim of reducing rural farmers’ poverty. The programme started in 2005 and has received enormous commendations from various international organisations for adopting this strategic of poverty reduction programme in contributing its quota to the poverty reduction agenda. This research therefore assessed the social and economic impact of the programme on participants by analysing primary data collected from both beneficiaries and non-beneficiaries of the programme using questionnaire. The data was analysed using budgeting techniques and multiple regression. The results show a significant difference of GH¢1,551.90 between participants mean gross margin and non-participants mean gross margin. Also, the results reveal a significant impact of the programme on participating farmers’ income besides the benefits of increases in the visits by extension agent, farm size, hired labour and fertilizer application. The joint explanation of the variables presented in the regression model was estimated to be 82.16%. The findings shows that inappropriate time of delivery of inputs, wasting of time in process loan among other were considered to be the weakness of the company. It is recommended that input should be deliver at the right time and at the right quantity based on the farm size.